Skill-mix Innovation, Effectiveness and Implementation Improving Primary and Chronic Care - Maier, Claudia B.; Kroezen, Marieke; Busse, Reinhard; Wismar, Matthias (Social Sciences, 2022)
Systemically analyses health workforce skill-mix innovations, implementation and outcomes by focusing on six core segments of health systems: health promotion and prevention, acute care, chronic care, long-term and palliative care, as well as access for vulnerable groups and people living in underserved areas.